Early ultrasonographic tumor regression after linear accelerator stereotactic fractionated photon radiotherapy of choroidal melanoma as a predictor for metastatic spread. Issue 3 (June 2018) - Mitsch, Christoph; Zehetmayer, Martin; Gleiss, Andreas; Georg, Dietmar; Dieckmann, Karin; Pötter, Richard; Sayegh, Ramzi; Schmidt-Erfurth, Ursula; Dunavoelgyi, Roman
Abstract: Background and purpose: During extended follow-up (of up to 15 years), approximately fifty percent of patients with choroidal melanoma will develop metastatic disease and eventually die. Thus, continuing research on prognostic factors, early detection and treatment is necessary. Height regression rates both after plaque brachytherapy and proton beam irradiation have been shown to have prognostic value. The purpose of this study was to analyze the influence of early tumor regression rate after treatment of choroidal melanoma with LINAC stereotactic fractionated radiotherapy (SFRT) as an independent risk factor for metastasis. Material and methods: 256 patients with choroidal melanoma treated with LINAC SFRT were included. Follow-up included standardized echography yielding apical height, smallest and largest basal linear diameter, tumor volume and mean reflectivity. The influence of baseline measurements and of a longitudinal, normalized area under the curve coefficient (NAC) of the latter marker on metastasis risk was assessed. Results: NAC for tumor thickness at months 3, 6, and 12 had a statistically significant ( p  < 0.001) non-linear effect on risk of metastasis. Additionally, ultrasonographic baseline tumor dimensions, but not internal reflectivity were found to be statistically significant risk factors for metastasis. Conclusions: Our results demonstrate a non-linear influence of regression rate of choroidal melanoma as independent risk factor of metastatic disease after LINAC SFRT. These prove the clinical experience that, in comparison to rather slow regressions, very quick and very slow early tumor responses to LINAC SFRT are associated with a significantly higher metastasis risk.